2022
DOI: 10.1155/2022/6000715
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Rainy Weather Effects on Driving Behaviour Dimensions of Driving Behaviour Questionnaire

Abstract: This study aims to develop a modified version of the existing driving behaviour questionnaire (DBQ) by including items related to driving behaviour under rainy conditions to evaluate driving behaviour changes and their implications. A survey of 680 drivers in Iran was conducted with the modified DBQ considering rainy conditions. Exploratory and confirmatory factor analysis concluded a four-factor solution (high velocity with a law violation, slips, positive and cautious behaviours, and aggressive driving behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…One study found that females may be superior to males at keeping within their lanes during foggy weather conditions, 30 and even in non-US contexts surveys suggest that male driving behaviors may exacerbate risks secondary to inclement weather. 31 …”
Section: Discussionmentioning
confidence: 99%
“…One study found that females may be superior to males at keeping within their lanes during foggy weather conditions, 30 and even in non-US contexts surveys suggest that male driving behaviors may exacerbate risks secondary to inclement weather. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The versatility and applicability of the SDBQ in different Spanish-speaking environments demonstrate that the questionnaire is a valuable tool in the fields of traffic psychology and road safety. The collaboration and effort of experts who have come from different countries to adjust and apply the SDBQ testify to the continued commitment of the scientific community to improving the understanding of human behavior on the road, which is fundamental to the development of policies and practices that improve transportation safety and efficiency throughout the Spanish-speaking world [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The innovation of the front brake light provides other road users with information about the braking of the vehicle. The front brake light is technically a green light [51], located at the front of the vehicle. The choice of the color green is due to the fact that there are certain colors of light that cannot be used, such as red for the rear brake light, blue for indicating the priority of passage, and orange for indicating the direction of travel of the vehicle.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several authors reported that driver characteristics (e.g., driver age, driver gender, marital status [51][52][53]) and their experience with means of transport (attitude towards driving, number of kilometers driven, experience with a traffic accident) play a significant role in driving behavior [54].…”
Section: Theoretical Backgroundmentioning
confidence: 99%